An air-stable, Zn2+-based catalyst for hydrosilylation of alkenes and alkynes. Issue 25 (1st June 2021) - Groutchik, Kristina; Jaiswal, Kuldeep; Dobrovetsky, Roman
Abstract : An air-stable, Zn 2+ -based catalyst for catalytic hydrosilylation reactions of alkenes and alkynes. Abstract : Hydrosilylation of CC double and CC triple bonds is one of the most widely used processes in organosilicon chemistry, mostly catalyzed by Pt-based complexes. We report here the synthesis of an air-stable dicationic Zn 2+ -based complex in a hemilabile tris(2-methyl-6-pyridylmethyl) phosphine (TmPPh) ligand, 1 2+ [B(C6 F5 )4 ]2 . When heated, 1 2+ [B(C6 F5 )4 ]2 activates Si–H bonds reversibly via ligand/metal cooperation between Lewis acidic Zn 2+ and Lewis basic N centers in a frustrated Lewis pair (FLP) type fashion. Consequently, 1 2+ [B(C6 F5 )4 ]2 was found to be an effective catalyst for hydrosilylation reactions of CC double and CC triple bonds. Remarkably, these hydrosilylation reactions can be loaded under aerobic conditions, as well as, in some cases, work under neat conditions. The mechanism of the activation of the Si–H bond and the hydrosilylation reaction is proposed based on experiments and density functional theory (DFT) calculations.